Analysis of Maintenance Management at PT.XYZ Power Plant (With MTTR, MTTF, and Availability Factors) and Development of Performance Improvement Program - Nurdiansyah, Dida; D.P, Agustinus Hariadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Damage data for machinery at PT. XYZ power plant between October-December 2023 shows that the pump is the component with the highest number of failures, recording 28 incidents (33.7% of the total 83 failures), followed by the condenser with 27 incidents (32.5%). The combined failures of these two components account for 66.3% of the total failures, indicating a need for focused improvements on the pump and condenser. The MTTR analysis for the pump shows a high average repair time: 7.7 hours in October, 7 hours in November, and 7.7 hours in December, with low availability rates (89.64%-89.69%). The MTTF for the pump varies from 65.2 to 75.4 hours, indicating the need for improved preventive maintenance strategies. It is recommended that maintenance be carried out every 2-3 days or at least once a week. The condenser has an MTTR ranging from 6.7 to 7.7 hours and low availability (88.89%-89.95%), with MTTF varying from 66.7 to 92.7 hours. The high MTTR and low availability of these two components highlight the need for improvements in maintenance management to enhance performance.